Mexico : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2018)
This Fiscal Transparency Evaluation (FTE) report assesses Mexico's fiscal transparency practices against the IMF's Fiscal Transparency Code (FTC), including the draft pillar on resource revenue management. Mexico scores relatively well when compared with other Latin American countries and emerging market economies that have undergone a FTE. Out of the 48 principles across four pillars in the FTC, Mexico meets 16 principles at the basic level, 9 principles at the good level and 15 principles at the advanced level, while one principle does not apply. Fiscal transparency practices are strongest in the areas of resource revenue management and fiscal forecasting and budgeting, while the scores on fiscal risks analysis and management are lower.